1999
DOI: 10.1093/ajcn/69.6.1202
|View full text |Cite
|
Sign up to set email alerts
|

Protein pulse feeding improves protein retention in elderly women

Abstract: A protein pulse-feeding pattern was more efficient than was a protein spread-feeding pattern in improving, after 14 d, whole-body protein retention in elderly women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
138
3
7

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 252 publications
(156 citation statements)
references
References 29 publications
7
138
3
7
Order By: Relevance
“…This phenomenon may partly explain reports [23,50 • ,51] that older adults require a higher protein intake or a protein 'pulse feeding' pattern, i.e. daily protein intake concentrated on one of the daily meals [52,53], to improve their nitrogen and amino acid balance.…”
Section: Amino Acids and Regulation Of Muscle Metabolism In Healthy Amentioning
confidence: 97%
“…This phenomenon may partly explain reports [23,50 • ,51] that older adults require a higher protein intake or a protein 'pulse feeding' pattern, i.e. daily protein intake concentrated on one of the daily meals [52,53], to improve their nitrogen and amino acid balance.…”
Section: Amino Acids and Regulation Of Muscle Metabolism In Healthy Amentioning
confidence: 97%
“…Our discussion focuses on the effects of the intervention as exploring pre-sarcopenia was the initial aim of this investigation. Many researchers performed investigations that focused on exercise and nutritional intake to control the decline of muscle mass and strength in patients with sarcopenia (Campbell, Crim, Dallal, Young, & Evans, 1994;Arnal et al, 1999;Kim et al, 2012;Rondanelli et al, 2016), but the results of these studies have not always been consistent (Kerstetter et al, 2005;Dillon et al, 2009;Paddon-Jones & Rasmussen, 2009). Our study demonstrates that the arm and leg muscle mass, hand grip strength, and walking speed did not increase with combined exercise and amino acid ingestion in both groups; however, the SMI improved only in the exercise and amino acid supplement group.…”
Section: Discussionmentioning
confidence: 99%
“…In older individuals, however, it appears that proteins that are rapidly digested and absorbed induce a better anabolic response as compared with the 'slower' proteins (Dangin et al 2002). Arnal et al (1999Arnal et al ( , 2000 found that the protein-feeding pattern is also important for optimal N retention. Specifically, they found that in older women protein pulse feeding induces a better N retention as compared with continuous feeding (Arnal et al 1999), whereas this is not true in younger individuals (Arnal et al 2000).…”
Section: Splanchnic Tissues and Muscle Protein Metabolism In The Elderlymentioning
confidence: 99%